Variability of isolates of Phoma sorghina in rice - Souza, Napoleão S. de; Zambolim, Laércio; Thiebaut, José T. L. (Pesquisa Agropecuaria Brasileira, 2014)
Studies on pathogenic variability in Phoma sorghina (Sacc.) Boerema, Dorenbosch & van Kesteren were conducted under greenhouse conditions using nine isolates. Inoculations were made by injecting 1 ml of spore suspension (2.3 x 106conidia/ml) with hypodermic syringe into the boots of rice cultivars. Ten days after inoculation the disease severity was evaluated. The cultivars showed different levels of resistance when they were inoculated with one isolate; differences in aggresivity were observed among the isolates when several isolates were tested on one cultivar.